5
$\begingroup$

So take the function $$f_{1}(x)=\sum_{n=3}^{x+2}n^x.$$ This will give results like $3^1$, for $x=1$, $3^2+4^2$, for $x=2$, and $3^3+4^3+5^3$, for $x=3$, and etc. Now, also, take the function $$f_2(x)=(x+3)^x.$$ This will give results like $4^1$, for $x=1$, $5^2$, for $x=2$, and $6^3$, for $x=3$, and etc.
Both of these kind of relate to Fermat's last theorem and Euler's related conjecture.
What's cool is that $f_1(x)=f_2(x)$, when $x=2,3$.
However, both functions separate at higher values, for example: $$f_1(4)=3^4+4^4+5^4+6^4=2258\neq f_2(4)=7^4=2401.$$ What is interesting, though, is that $f_2(x)\ge f_1(x)$, for all non-negative integer $x$ ($f_1$ wouldn't even make sense with any other domain).
Even more interesting is the function $\frac{f_2(x)}{f_1(x)}$, which appears to converge, as $x$ approaches infinity.
Her is a table of values for $x$, $f_1(x)$, $f_2(x)$, and $\frac{f_2(x)}{f_1(x)}$ (values are 5 digit approximations) $$ \begin{array}{c|lcr} x & f_1(x) & f_2(x) & \frac{f_2(x)}{f_1(x)} \\ \hline 1 & 3 & 4 & 1.3333 \\ 2 & 25 & 25 & 1 \\ 3 & 216 & 216 & 1 \\ 4 & 2258 & 2401 & 1.0633 \\ 5 & 28975 & 32768 & 1.1309 \\ 10 & 1.0277\times 10^{11} & 1.3786\times 10^{11} & 1.3414 \\ 20 & 1.1446\times 10^{27} & 1.7162\times 10^{27} & 1.4994 \\ 30 & 2.2970\times 10^{45} & 3.5927\times 10^{45} & 1.5641 \\ 40 & 1.3640\times 10^{65} & 2.1814\times 10^{65} & 1.5993 \\ 50 & 1.0090\times 10^{86} & 1.6360\times 10^{86} & 1.6214 \\ 100 & 1.1521\times 10^{201} & 1.921\times 10^{201} & 1.6681 \\ 142 & 4.8786\times 10^{306} & 8.2083\times 10^{306} & 1.6825 \\ \end{array} $$ So the question comes down to:$$\text{What is} \lim_{x\to \infty} \frac{(x+3)^x}{\sum_{n=3}^{x+2}n^x}?$$

$\endgroup$
3
$\begingroup$

0. Opening: Note that $$f_1(x)=\sum_{n=3}^{x+2}n^x=(x+2)^x\sum_{k=0}^{x-1}\left(1-\frac k{x+2}\right)^x$$ 1. Upper bound: For every $t$, $$1-t\leqslant e^{-t}$$ hence, for every $k$, $$\left(1-\frac k{x+2}\right)^x\leqslant e^{-kx/(x+2)}$$ which implies $$f_1(x)\leqslant(x+2)^x\sum_{k=0}^\infty e^{-kx/(x+2)}=\frac{(x+2)^x}{1-e^{-x/(x+2)}}$$ hence $$\frac{(x+3)^x}{f_1(x)}\geqslant\left(1+\frac1{x+2}\right)^x(1-e^{-x/(x+2)})=g(x)$$ 2. Lower bound: On the other hand, for every $t$ in $(0,\frac12)$, $$1-t\geqslant e^{-t-t^2}$$ Fix some positive $a$. Then, for every $k\leqslant a\sqrt x$ and every $x$ large enough, $$\left(1-\frac k{x+2}\right)^x\geqslant e^{-kx/(x+2)}e^{-a^2}$$ which implies $$f_1(x)\geqslant(x+2)^xe^{-a^2}\sum_{k=0}^{a\sqrt x}e^{-kx/(x+2)}\geqslant(x+2)^xe^{-a^2}\frac{1-e^{-a\sqrt xx/(x+2)}}{1-e^{-x/(x+2)}}$$ hence $$\frac{(x+3)^x}{f_1(x)}\leqslant\left(1+\frac1{x+2}\right)^xe^{a^2}\frac{1-e^{-x/(x+2)}}{1-e^{-a\sqrt xx/(x+2)}}=h_a(x)$$ 3. Cauda: Now, $$\lim_{x\to\infty} g(x)=e(1-e^{-1})=e-1$$ and $$\lim_{x\to\infty} h_a(x)=e\,e^{a^2}\frac{1-e^{-1}}{1}=(e-1)e^{a^2}$$ hence, for every positive $a$, $$e-1\leqslant\liminf_{x\to\infty}\frac{(x+3)^x}{f_1(x)}\leqslant\limsup_{x\to\infty}\frac{(x+3)^x}{f_1(x)}\leqslant(e-1)e^{a^2}$$ which, in the limit $a\to0$, implies

$$\lim_{x\to\infty}\frac{(x+3)^x}{f_1(x)}=e-1$$

$\endgroup$
  • $\begingroup$ I don't realize why a must approach zero at the end. How did you come to the first conclusion under section 2: lower bound? Where a is introduced? $\endgroup$ – Roked Mar 26 '18 at 15:10
  • $\begingroup$ "Where a is introduced?" When the text says "Fix some positive $a$". "why a must approach zero at the end" The parameter $a$ "must" not do anything, only, the upper bound by $h_a(x)$ holds for every $a>0$, hence we consider the tighter upper bound one can deduce from these, which is their infimum (and also their limit when $a\to0$). $\endgroup$ – Did Mar 26 '18 at 15:35
2
$\begingroup$

Not an answer but just for the fun of playing with huge numbers and illimited precision.

Let $x=10 ^k$ and compute the expression as you did. This gives $$\left( \begin{array}{cc} k & \text{result} \\ 1 & 1.341438740 \\ 2 & 1.668056114 \\ 3 & 1.713087849 \\ 4 & 1.717760654 \\ 5 & 1.718229693 \\ 6 & 1.718276615 \\ 7 & 1.718281307 \end{array} \right)$$ which looks like $(e-1) \approx 1.718281828$.

My computer (and I) gave up for $k=8$. However, using Aitken acceleration $$p_8= p_5-\frac{(p_6-p_5)^2}{p_7-2 p_6+p_5}$$and more decimal figures for the previous calculations, the next term would be $1.71828182848$ while $(e-1) \approx 1.718281828459$.

$\endgroup$
0
$\begingroup$

Not an answer but just for fun and to explore others ways

By Cesaro-Stolz

$$\frac{a_x}{b_x}=\frac{(x+3)^x}{\sum_{n=3}^{x+2}n^x}\implies \frac{a_{x+1}-a_x}{b_{x+1}-b_x}=\frac{(x+4)^{x+1}-(x+3)^x}{\sum_{n=3}^{x+3}n^{x+1}-\sum_{n=3}^{x+2}n^x} =\frac{(x+4)^{x+1}-(x+3)^x}{(x+3)^{x+1}+\sum_{n=3}^{x+2}\left(n^{x+1}-n^x\right)} =\frac{(1+\frac1{x+3})^{x+1}-\frac1{x+3}}{1+\frac{\sum_{n=3}^{x+2}\left(n^{x+1}-n^x\right)}{(x+3)^{x+1}}}$$

then if $\lim_{x\to\infty} \frac{\sum_{n=3}^{x+2}\left(n^{x+1}-n^x\right)}{(x+3)^{x+1}}=L_2 \implies L_1=\lim_{x\to \infty} \frac{(x+3)^x}{\sum_{n=3}^{x+2}n^x}=\frac{e}{1+L_2}$

then again by Cesaro-Stolz we obtain

$$\frac{a_x}{b_x}=\frac{\sum_{n=3}^{x+2}\left(n^{x+1}-n^x\right)}{(x+3)^{x+1}}=\frac{\sum_{n=3}^{x+2} n^x(n-1)}{(x+3)^{x+1}}\implies \frac{a_{x+1}-a_x}{b_{x+1}-b_x} =\frac{\sum_{n=3}^{x+3} n^{x+1}(n-1)-\sum_{n=3}^{x+2} n^x(n-1)}{(x+4)^{x+2}-(x+3)^{x+1}} =\frac{(x+3)^{x+1}(x+2)+\sum_{n=3}^{x+2} n^{x}(n-1)^2}{(x+4)^{x+2}-(x+3)^{x+1}} =\frac{1+\frac{\sum_{n=3}^{x+2} n^{x}(n-1)^2}{(x+3)^{x+1}(x+2)}}{\frac{x+4}{x+2}(1+\frac1{x+3})^{x+1}-\frac1{x+2}}$$

thus if $\lim_{x\to\infty} \frac{\sum_{n=3}^{x+2} n^{x}(n-1)^2}{(x+3)^{x+1}(x+2)}=L_3 \implies L_2=\frac{1+L_3}{e}$

then again by Cesaro-Stolz we obtain

$$\frac{a_x}{b_x}=\frac{\sum_{n=3}^{x+2} n^{x}(n-1)^2}{(x+3)^{x+1}(x+2)}\implies \frac{a_{x+1}-a_x}{b_{x+1}-b_x} =\frac{\sum_{n=3}^{x+3} n^{x+1}(n-1)^2-\sum_{n=3}^{x+2} n^{x}(n-1)^2}{(x+4)^{x+2}(x+3)-(x+3)^{x+1}(x+2)} =\frac{(x+3)^{x+1}(x+2)^2+\sum_{n=3}^{x+2} n^{x}(n-1)^3}{(x+4)^{x+2}(x+3)-(x+3)^{x+1}(x+2)} =\frac{1+\frac{\sum_{n=3}^{x+2} n^{x}(n-1)^3}{(x+3)^{x+1}(x+2)^2}}{\frac{(x+4)(x+3)}{(x+2)^2}(1+\frac1{x+3})^{x+1}-\frac1{x+2}} $$

thus if $\lim_{x\to\infty} \frac{\sum_{n=3}^{x+2} n^{x}(n-1)^3}{(x+3)^{x+1}(x+2)^2}=L_4 \implies L_3=\frac{1+L_4}{e}$

If we assume for true that $L_2$, $L_3$ and $L_4$ exist and $L_2=L_3=L_4$ we obtain that

$$L_2=\frac{1+L_2}{e}\implies eL_2-L_2=1 \implies L_2=\frac{1}{e-1}$$

and then

$$L_1=\lim_{x\to \infty} \frac{(x+3)^x}{\sum_{n=3}^{x+2}n^x}=\frac{e}{1+\frac{1}{e-1}}=\frac{e(e-1)}{e-1+1}=e-1$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.